In Search of the Labyrinth : The Cultural Legacy of Minoan Crete - Momigliano, Nicoletta (New Directions in Classics Ser, 2020)
Cover page -- Halftitle page -- Series page -- Title page -- Copyright page -- Dedication -- Contents -- Illustrations -- Preface and Acknowledgements -- 1 Introduction: Desperately Seeking Ariadne - the Cultural Legacy of Minoan Crete1 -- 2 Sons of Europa: From Medical Remedies for Constipation to Bestiality, Sexually Transmitted Death, and the Dawn of the 'Minoan Age' (from Antiquity to the Mid-Nineteenth Century) -- Ancient responses to Minoan Crete -- From Arab to Ottoman: Responses to Minoan material culture c. 824-1860, and the dawn of the 'Minoan Age' -- 3 Rediscovering European Origins: Ariadne as the Great Mother Goddess (Mid-Nineteenth Century-First World War) -- The Schliemann factor -- From the tomb of Agamemnon to the palace of Minos -- 'Little Evans - son of John Evans the Great' and the road to Knossos45 -- From the Palace of Minos to the Palace of Ariadne: Κρητική Πολιτεία (Cretan State) (1898-1913) and the Heroic Age of Cretan excavations -- All aboard! The Minoans in the late Belle Époque -- Cretomania in the late Belle Époque: The Minoans in modern cultural practices c. 1900-1918 - Neo-Minoans from Crete to Paris and beyond -- Conclusions: The romance and triumph of Minoan Crete, the decadence of Mycenaean Greece -- 4 Minoans and the World Wars (c. 1915-49): The Aryan Revenge -- Crete from the Kritiki Politeia to the Second World War and its aftermath -- From pan-Minoan Aegean to 'Minoans go home!' - the return of the Aryans and the decline and fall of the Minoan Empire -- Cretomania amidst World and Civil Wars: The Minoans in modern cultural practices c. 1918-1949 - from decadence to hope for the future -- Conclusions: The Minoans in an age of extremes and catastrophes -- 5 The Minoans in the Cold War and Swinging Sixties: From the End of the Greek Civil War to the End of the Colonels' Dictatorship (c. 1949-74).